Correction of Constricted Ear – Case Report - Damjanoska Krstikj, Ljubinka; Rajkovska Kimovska, Ana; Krsteska, Roza; Stevkovska, Mare (Lietuvos chirurgija, 2024)
Introduction. Congenital deformities of the outer ear are common; reported incidence are from 1:6000 to 1:6830 newborns. Multitude of corrective procedures are described in the literature. Purpose of the case study. The adequate surgical treatment of the congenital constricted ear remains a challenge. Selected tailor made approach should be employed on case by case basis, thus, in this study we present our case of moderate constricted ear and the used surgical procedures done under general anesthesia, as well as the outcome of the treatment. Case report. A 6 year old girl presented in pediatric and plastic surgery department with complaint of right ear deformity from birth and additional psychological effects such as increased difficulty in social integration and lack of self- confidence. On clinical examination, we considered as constricted ear grade IIB by Tanzel. Two separate procedures under general anesthesia were done. In the first procedure, advancement of the helix and otoplasty was performed; an effective expansion, of about 1 cm in the length of the pinna was obtained. In the second procedure, about 0.5 cm expansion of the helix was performed, and also the breadth of the pinna. Conclusion. In our case, combination of Mustardé suture, helix advancement and helix cartilage graft in moderate constricted ear were a useful surgical option, producing aesthetically good results in a simple and effective way.